The particulate matter caused excess mortality in 22 hungarian city - Szuhi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Air pollution raise the mortality and morbidity. In our work we estimate the PM10 caused excess mortality in 2007. On the base of the data of National Air Pollution Monitoring Network, using the method suggested by the World Health Organization, and chosing the proper exposition-response fuction it is possible to estimate the excess mortality caused by particulate matter. We calculated that 4891 excess mortality happen because of air pollution in 22 hungarian town, which give the 1/3 of the hungarian population. Our results show that air pollution has a considerable role in the unfavourable hungarian mortality statictics. In the future we need to use transmission modelling based on emission-inventories considering spatial parameters in order to refine the results and achive data from non-examined areas.